ISSUES OF DEVELOPMENT OF THE TEXTILE AND SEWINGKNITTING INDUSTRY ENTERPRISES’ QUALITY MANAGEMENT SYSTEMS AND IMPROVEMENT OF METHODS FOR ITS EVALUATION - Khalilov Nurullo Khamidillayevich; Nafisa Safina (Scholar Express Journals, 2024)
The article substantiates the importance of developing a quality management system for textile and sewing-knitting industry enterprises in the digital economy, improves methods for its assessment, and, based on the analysis, develops a strategy and model for the development of a quality management system.
Keywords: management; substantiates; importance